2009
DOI: 10.1128/aem.01974-08
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Molecular Diversity of Copper-Zinc Superoxide Dismutase Genes among and within Species of Arbuscular Mycorrhizal Fungi

Abstract: In the ecologically important arbuscular mycorrhizal fungi (AMF), Sod1 encodes a functional polypeptide that confers increased tolerance to oxidative stress and that is upregulated inside the roots during early steps of the symbiosis with host plants. It is still unclear whether its expression is directed at scavenging reactive oxygen species (ROS) produced by the host, if it plays a role in the fungus-host dialogue, or if it is a consequence of oxidative stress from the surrounding environment. All these poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Interestingly, some isolates of G. intraradices from a natural population were shown to harbor very divergent orthologous SOD1 sequences (Corradi et al 2009). It has been hypothesized that this high rates of protein evolution might be driven by evolutionary forces to facilitate interactions with the host plants at an organismic (colonization of root tissues) and/or ecosystem (widening the host range) level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some isolates of G. intraradices from a natural population were shown to harbor very divergent orthologous SOD1 sequences (Corradi et al 2009). It has been hypothesized that this high rates of protein evolution might be driven by evolutionary forces to facilitate interactions with the host plants at an organismic (colonization of root tissues) and/or ecosystem (widening the host range) level.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted protein has 157 amino acid residues with a molecular mass of 16.3 kDa. The deduced amino acid sequence is closely related to fungal CuZnSOD homologs, showing the highest similarity to partial CuZnSOD gene sequences from different Glomus species (98-80% identity; Corradi et al 2009), 73% similarity to the G. margarita homolog (Lanfranco et al 2005) and approximately 70% similarity to sequences from ascomycotan CuZnSODs. An alignment of the GintSOD1 protein sequence with those from the AM fungus G. margarita, the ericoid mycorrhizal fungus Oidiodendrom maius and the ascomycetes Paecilomyces tenuipes, Claviceps purpurea, S. cerevisiae and Aspergillus niger revealed that it contains features characteristic of CuZnSOD proteins, such as the conserved histidine and aspartate residues essential for dismutation and metal binding (Fig.…”
Section: Sequence Analysis Of Gintsod1mentioning
confidence: 94%
“…In addition, most AMF species contained Sod1 genes that are upregulated inside roots and imparts drought tolerance to host plants (Corradi et al 2009). Higher activity of SOD suggests that AMF plants possessed more efficient superoxide dismutation in line with decreasing soil water content so that more effective detoxification of superoxide radicals into H 2 O 2 takes place (Zou et al 2015).…”
Section: Amf Colonization In Roots Of Plants Subjected To Drought Stressmentioning
confidence: 99%
“…However, one gene, the superoxide dismutase, Sod1, that is up-regulated in the fungus during the development of the symbiosis has been identified in AMF (56). Interestingly, this gene shows extremely high variability in AMF, even among isolates of G. intraradices from one field (17). What is even more striking about the variation is that it appears to be subject to diversifying selection where variants have high levels of substitutions leading to changes in the amino acid sequence of the protein.…”
Section: Understanding Arbusculuar Mycorrhizal Fungi Genetics Is a Prmentioning
confidence: 99%